Microsoft SQL Server - Gray, Jim (1997)
Providing users with 100% availability has been a top priority for IT managers for years. Microsoft Cluster Server (MSCS), which is a feature of Microsoft Windows NT Server, Enterprise Edition , provides the platform required for you to achieve this goal. SQL Server takes full advantage of the capabilities of MSCS. It provides IT managers with a reliable and robust platform on which they can build their mission-critical applications. This whitepaper discusses MSCS, current methods of achieving high-availability for database systems, how SQL Server 6.5 and the upcoming release of SQL Server will provide high-availability, scalability and maintainability and what the future holds for this technology.